Building and sustaining mentor interactions as a mentee. (5th April 2021) - Sarabipour, Sarvenaz; Hainer, Sarah J.; Arslan, Feyza Nur; de Winde, Charlotte M.; Furlong, Emily; Bielczyk, Natalia; Jadavji, Nafisa M.; Shah, Aparna P.; Davla, Sejal
Abstract : Mentorship is experience and/or knowledge‐based guidance. Mentors support, sponsor and advocate for mentees. Having one or more mentors when you seek advice can significantly influence and improve your research endeavours, well‐being and career development. Positive mentee–mentor relationships are vital for maintaining work–life balance and success in careers. Early‐career researchers (ECRs), in particular, can benefit from mentorship to navigate challenges in academic and nonacademic life and careers. Yet, strategies for selecting mentors and maintaining interactions with them are often underdiscussed within research environments. In this Words of Advice, we provide recommendations for ECRs to seek and manage mentorship interactions. Our article draws from our experiences as ECRs and published work, to provide suggestions for mentees to proactively promote beneficial mentorship interactions. The recommended practices highlight the importance of identifying mentorship needs, planning and selecting multiple and diverse mentors, setting goals, and maintaining constructive, and mutually beneficial working relationships with mentors. Abstract : How can early‐career researchers source mentors and manage mentorship expectations? This Words of Advice article provides guidance to researchers to identify mentors at all career stages and maintain relationships with their mentors. We recommend identifying mentorship needs, planning and selecting multiple and diverse mentors, setting goals and maintaining positive, constructive and mutually beneficial working interactions with mentors.